PENGARUH PELATIHAN KERJA DAN KOMPENSASI TERHADAP MOTIVASI KERJA SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN - Ayu Lestari Purnamasari; Rifki Meilianda; Karnawi Kamar; Marhaendro Purno (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
The goal of this research is to understand the impact of job training and compensation on work motivation and employee performance. A total of 84 employees from PT. Dongseo Furniture participated as respondents and completed questionnaires for data collection. The data was further analyzed using correlation tests (both partial and simultaneous), determination coefficient tests (partial and simultaneous), and regression tests (simple and multiple). Hypothesis tests (t-test and F-test) were conducted at a 5% significance level (Î± = 5%). The findings, processed using SPSS version 23, reveal a significant influence of job training and compensation on work motivation and employee performance.Â Keywords: Compensation, Employee Performance, Job Training, Work Motivation